Answer:
A
Explanation:
Our equation is:
![(2)/(3) *((1)/(2) x+12)=(1)/(2) *((1)/(3) x+14)-3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/99c0qauebkkhc0e58px9ux2n6pwqxx4idv.png)
Let's first distribute the left side. When distributing, we essentially find the sum of the product of the outside term with each of the inside terms. Here, the outside term is 2/3 and the inside terms are 1/2x and 12. So:
![(2)/(3) *((1)/(2) x+12)=(2)/(3) *(1)/(2) x+(2)/(3) *12=(1)/(3) x+8](https://img.qammunity.org/2021/formulas/mathematics/middle-school/78626mwdm6ob6pdlvy67lavdkln0t11xas.png)
Now distribute the right side. Here, the outside term is 1/2 and the inside terms are 1/3x and 14, so:
![(1)/(2) *((1)/(3) x+14)-3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/k163sqnlt0j5t7f3qeri0wvbhm3pc7t13o.png)
![(1)/(2) *((1)/(3) x+14)-3=(1)/(2) *(1)/(3) x+(1)/(2) *14-3=(1)/(6) x+7-3=(1)/(6) x+4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/k40w0yuq76sijalsvtgmwma6s08l2u8hwx.png)
We now have:
![(1)/(3) x+8=(1)/(6) x+4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/puoyvvvx7x7g9izmmldtsf0q2c6gusbmq8.png)
Isolate the variable by bringing 1/6x to the left and bringing 8 to the right:
![(1)/(3) x-(1)/(6) x=4-8](https://img.qammunity.org/2021/formulas/mathematics/middle-school/jxs7qui1dfhm137lgomgxgytgyawv11d3p.png)
![(2)/(6) x-(1)/(6) x=-4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/fo7nyf58l8j9n3woapk3ok8o94atddzujt.png)
![(1)/(6) x=-4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/shc5hu601yo9wt058mmeqxpn5js2jbpikq.png)
x = -4 * 6 = -24
The answer is A.